Associations between occupational relative aerobic workload and resting blood pressure among different age groups: a cross-sectional analysis in the DPhacto study - Andreas Holtermann; Nidhi Gupta; Mette Korshøj; Els Clays; Niklas Krause; Marie Birk Jørgensen (BMJ Open)
Objective High levels of occupational physical activity (OPA) increase heart rate, blood pressure (BP) and the risk of hypertension. Older workers may be more vulnerable to high levels of OPA due to age-related degeneration of the cardiovascular system and cardiorespiratory fitness. This study investigates the association of relative aerobic workload (RAW) with resting BP and examines if this relation is moderated by age.Design Cross-sectional epidemiological study.Setting Data were collected among employees of 15 Danish companies in the cleaning, manufacturing and transport sectors.Participants 2107 employees were invited for participation, of these 1087 accepted and 562 (42% female and 4% non-Westerns) were included in the analysis based on the criteria of being non-pregnant, no allergy to bandages, sufficient amount of heart rate data corresponding to ≥4 work hours per workday or 75% of average work hours, and no missing outcome and confounder values.Primary and secondary outcome measures The primary outcome measure was BP.Results Heart rate reserve was estimated from ambulatory 24-hour heart rate measures covering 2.5 workdays per participant (SD 1.0 day). Age significantly moderated the association between RAW and BP. Mean intensity and duration of high RAW (≥30% heart rate reserve) showed positive associations with diastolic BP and negative associations with pulse pressure (PP) among participants ≥47 years old. Tendencies towards negative associations between RAW and BP were seen among participants <47 years old.Conclusions Mean intensity and duration of RAW increased diastolic BP among participants ≥47 years old. Negative associations with PP may be due to healthy worker selection bias. Prevention of hypertension should consider reductions in RAW for ageing workers.